Development of the Algorithm for 3D Cephalometric Analysis of Planning Surgical Interventions for Congenital and Acquired Defects and Deformities of the Facial Skeleton - M. Gusarov, Artem; Yu. Ivanov, Sergey; A. Muraev, Alexander; V. Ermolin, Dmitry; V. Bykovskaya, Tatiana (International Journal of Psychosocial Rehabilitation, 2020)
Planning surgery for congenital and posttraumatic injuries to the bones of the facial skeleton is an important task that often determines success in treatment. Since the structure of the facial skeleton is complex and soft tissues vary in thickness, it is very difficult to plan the outcome of surgical treatment. The authors have developed 3DCef software and a 3D-cephalometric analysis algorithm, which is based on this program. The authors carried out a cephalometric analysis of 40 MSCTs of the facial skeleton using the 3DCef program among patients of different ages and genders. The results of the study have revealed the minimum, maximum, and average values of cephalometric parameters. The authors have calculated the correlation values of the position of cephalometric points for the right and left sides of the face.